Clinicoepidemiological Findings and Pathological Characteristics of Different Types of Cutaneous Warts - Abdullah, Hawkar Ibrahim; Hassan, Ali Hussein (Kurdistan Journal of Applied Research, 2025)
Cutaneous warts, which result from infections by human papillomaviruses, are a common skin disease worldwide. They are categorized as  common, plantar, plane, genital, filiform, periungual and mosaic warts. Genital warts represent the most common sexually transmitted infections; however,  no sufficient information are available in Iraqi Kurdistan region, concerning their frequency rates; therefore, this study aims to determine the epidemiological and clinical features of patients with warts in this region, with special emphasis on estimating the frequency rates of genital warts and on analyzing their histopathological characteristics. A specially designed questionnaire was designed to collect socio-demographic and clinical data, such as age, gender, occupation, education and residency, from 420 patients with wart, together with the type and anatomical location of the warts. In addition, histopathological examination was performed for 20 patients with genital warts. Out of the total number of wart patients involved in this study, 255 were males, and 165 were females. Common warts were the most common type (39.0%) followed by the plantar and genital warts (30.5% and 11.9% respectively). Students were the most common individuals affected by the warts (46.0%), followed by self-employed persons (29.5%). Among patients with genital warts, most of the wart lesions were seen in multiple locations around the genital organs, and the papular form was the most frequent type seen. Histopathological examination of the genital wart lesions showed papillomatosis, acanthosis, koilocytosis, dysplasia, parakeratosis, and one case of squamous cell carcinoma in situ.